QUALITY INDICATORS OF WOOL FIBER - M. Turanov; A. Gaziev (International Engineering Journal For Research & Development, 2021)
The article examines the quality of red and black lambs in diamond and silver colours, as well as data from observations of similarities and differences in the results.